2021
DOI: 10.2174/1573403x15666190730094215
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 Inhibitors and Cardiovascular Outcomes: Do They Differ or There is a Class Effect? New Insights from the EMPA-REG OUTCOME trial and the CVD-REAL Study

Abstract: : A new group of hypoglycemic drugs has been used to treat diabetes type 2. This group is active sodium glucose co-transporter (SGLT2) or SGLT2 inhibitors. It has been shown that besides the treatment of diabetes, this drug class is responsible for the mildness of the cardiovascular events shown in patients with diabetes type 2. However, there is an intriguing question regarding the range of SGLT2 inhibitors and if there is a difference between them or if there is a class effect among their results. EMPA-REG O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Recent literature has reported the impact of Sodium-Glucose Co-transport 2 (SGLT-2) inhibitors in reducing ASCVD-related morbidity and mortality, especially among patients suffering with Diabetes Mellitus. 20,21 Furthermore, various studies have also advocated the use of Glucagon-like peptide 1 (GLP-1) receptor agonists cardiovascular and all-cause mortality. 17,[22][23][24] Nonetheless, none of our patients were on the aforementioned medications.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has reported the impact of Sodium-Glucose Co-transport 2 (SGLT-2) inhibitors in reducing ASCVD-related morbidity and mortality, especially among patients suffering with Diabetes Mellitus. 20,21 Furthermore, various studies have also advocated the use of Glucagon-like peptide 1 (GLP-1) receptor agonists cardiovascular and all-cause mortality. 17,[22][23][24] Nonetheless, none of our patients were on the aforementioned medications.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies indicate that improvements in T2DM management have led to significant reductions in diabetes-associated cardiovascular morbidity [36]. More recently, a new class of antidiabetic pharmaceuticals known as sodium glucose co-transporter (SGLT2) inhibitors have exhibited promise in ameliorating T2DM symptoms as well as reducing cardiovascular complications [37]. These preliminary improvements can potentially be further propelled if epigenetics is also considered.…”
Section: Type 2 Diabetes Mellitus (T2dm)mentioning
confidence: 99%
“…To reduce the risks of cardiovascular diseases, current clinical guidelines highlight the importance of a multifactorial approach in diabetic management, including the use of anti-diabetic agents [2,3]. The current literature suggests that novel anti-diabetic medications such as sodium-glucose cotransporter-2 inhibitors (SGLT2I) and glucagon-like peptide receptor agonists (GLP1a) demonstrate promising protective effects against various major adverse cardiovascular events (MACE) and mortality [4][5][6]. Some studies suggested that the cardiovascular benefit of SGLT2I and GLP1a is enhanced when used in conjunction [7].…”
Section: Introductionmentioning
confidence: 99%